Karakteristik dan aktivitas antibakteri minyak atsiri daun cengkeh dari daerah cluwak terhadap bakteri Staphylococcus aureus ATCC 25923 - Rahmawati , Laily Mega; Januarti , Ika Buana; Assidiqi , Elok Rosita; Rosyida , Raissa (Journal of Pharmaceutical and Sciences, 2025)
Essential oil is a potential wealth of Indonesia's natural resources as a raw material for medicines and cosmetics. Cengkeh leaf essential oil contains the main component of eugenol as an antibacterial. The purpose of this study was to determine the characteristics and antibacterial activity of cengkeh leaf essential oil from Cluwak region against Staphylococcus aureus ATCC 25923 bacteria. Cengkeh leaf essential oil was distilled by water vapor distillation method. Characterization of essential oil was performed on refractive index, optical rotation, and compound component analysis by GC-MS. Antibacterial activity was tested by the well diffusion method to obtain the diameter of inhibition at each concentration. Cengkeh leaf essential oil has a refractive index of 1.5303 and an optical rotation of 0.55. Analysis of the main components of the essential oil contains 7 main compound components with the highest compound m-eugenol. The diameter values of inhibition in antibacterial activity with concentrations of 10%, 20%, and 40% were 9.44 mm, 11.48 mm, and 12.37 mm, respectively. The characteristics of the essential oil are in accordance with the standard and the antibacterial activity is categorized as weak inhibition.